TANGGUNG JAWAB HUKUM RSUD TORA BELO KABUPATEN SIGI TERHADAP PELAYANAN KESEHATAN MASYARAKAT - Lossa, Christine (Katalogis, 2016)
Hospital is a health institution that should be able to provide optimal health care to patients with its duty to provide facilities and infrastructure needed to support health care. Based on the research results obtained in this thesis show that the implementation the liability in the Tora Belo hospital has not been implemented properly, therefore the Tora Belo hospital must be liability civil law in the Civil Code, are criminally liability pursuant to Law No. 36 of 2009 on Health and is liability for the administration according to Law No. 44 of 2009 on Hospitals. The factors that support and hinder the implementation of the liability of the hospital in Tora Belo responsible by using systems theory approach to the concept of law according to Lowrance M. Friedman covers the substance, structure and culture, so that the obtained results that the factors that hinder the implementation of the liability of the Tora Belo hospital is the factor structure and culture, while supporting factor is the factor of the substance.